Income convergence, migration and geography: Distribution analysis of regions in Norway - Hildegunn Stokke; Jorn Rattso (European Regional Science Association (ERSA), 2010)
Empirical evidence about income convergence among regions and countries is inconclusive and it is necessary to clarify the economic and institutional conditions for convergence. We investigate movements in the income distribution among regions in an integrated market with high mobility of labor, capital, knowledge and technology - municipalities and economic regions in Norway. Large and persistent population flows from the periphery towards urban centers characterize the economic development. The convergence towards a narrower unimodal distribution of per capita income is convincing in this homogenous institutional setting. Kernel density functions and finite first order Markov chains are estimated and tested, in particular with respect to the role of migration. Interestingly, migration seems to be unimportant for the convergence process, at odds with the recent emphasis on agglomeration effects and divergence. The population flows to urban centers do not generate growth processes where the income level in cities takes off compared to the periphery. The convergence process is slow, however, and the evolving regional income pattern seems to reflect differences in permanent regional factors.
Keywords: C26; D92; F2; J61; O15; O18; R11; R23; 330; Convergence; migration; divergence; agglomeration; Kernel density functions; Markov chains